Depression symptoms during pregnancy and postpartum in patients with recurrent pregnancy loss and infertility: The Japan environment and children's study. (August 2022) - Otani-Matsuura, Ayano; Sugiura-Ogasawara, Mayumi; Ebara, Takeshi; Matsuki, Taro; Tamada, Hazuki; Yamada, Yasuyuki; Omori, Toyonori; Kato, Sayaka; Kano, Hirohisa; Kaneko, Kayo; Matsuzaki, Kazuki; Saitoh, Shinji; et al.
Abstract: There are a limited number of studies in which the depression status was followed up throughout pregnancy and postpartum to 1 year after delivery though 8.6–33% of women with recurrent pregnancy loss (RPL) and 10–25% of women who undergo in vitro fertilization and embryo transfer (IVF-ET) suffer from depression. We examined whether RPL and IVF-ET affect depressive symptoms during pregnancy and postpartum. A nationwide large-scale birth cohort study known as the "Japan Environment and Children's Study (JECS)" was conducted. The subjects consisted of 99, 202 pregnant women recruited between January 2011 and March 2014. The Kessler Psychological Distress Scale was used for the 1st trimester, 2nd/3rd trimester and 1 year postpartum. The Edinburgh Postnatal Depression Scale was used for the first and the sixth month postpartum. The screening instruments were used to quantify depressive symptoms. Women with no live births had a significantly higher prevalence of elevated depressive symptoms throughout pregnancy and postpartum. The prevalence of elevated depressive symptoms was significantly higher in the second/third trimester among women with three or more pregnancy losses with no live births. IVF-ET was associated with reduced risk of developing depressive symptoms during all pregnancies and at 1 and 6 months after delivery in women with no live births. RPL and IVF-ET did not affect postpartum depressive symptoms, and IVF-ET rather reduced the risk of depression throughout pregnancy and postpartum. Psychological support for RPL women would be necessary. Highlights: Recurrent pregnancy loss (RPL) and IVF-ET did not affect postpartum depression symptoms. IVF-ET rather reduced the risk of depression symptoms throughout pregnancy and postpartum. The prevalence of depression symptoms in the second/ third trimesters was significantly increased in RPL women. Those with no previous live births had a higher prevalene of depression symptoms throughout pregnancy and postpartum.